"I've Tried and I've Died This Year": First-Year Teachers Reflect on Literacy Reform. Issue 1 (2nd January 2017) - Broemmel, Amy D.; Swaggerty, Elizabeth A.
ABSTRACT: This article describes the challenges associated with outcomes-based education reform as experienced by two novice elementary teachers. Interviews with the teachers provide insights into the tensions between their teaching beliefs and the practices employed in their local contexts. Specifically, pressures to both focus on standardized measures of student achievement and to conform to the social norms of the schools are explored. The authors advocate for the need for situated discussions about these tensions during the first year of teaching and recognition of the complexity of teaching and learning by all stakeholders.